Korelasi Kebijakan Dividen, Ukuran Perusahaan dan Profitabilitas Terhadap Kebijakan Hutang pada Perusahaan Manufaktur - Zefriyenni; Sari, Vivi Nila; Utami, Selvida (SAFE-Network, 2019)
This study aims to analyze how much the correlation between dividend policy, company size, and profitability is partially and simultaneously on debt policy. The data processed amounted to 161 companies. Data collection techniques through documentation study with secondary data accessed through the official website of the Indonesia Stock Exchange (IDX). The sampling technique uses purposive sampling method. The analytical method used is multiple linear regression. The results of this study indicate that dividend policy is not partially correlated significantly to debt policy, while company size and profitability are significantly correlated to debt policy. The coefficient of determination shows a value of 0.748 with a value of 74.8%. While the remaining 25.2% by factors in external variables.